Peran Guru sebagai Agen Perubahan dalam Menghadapi Tantangan Globalisasi Pendidikan - Haniatul kiromah; Abdul Khobir; Miftah Rizqi Amalia; Aqibul Muttaqin; Arsyadul Kirom (Yayasan Al-Afif, 2025)
The era of globalization has brought great changes in all aspects of human life, including the world of education. This change demands a new role of teachers as change agents that not only focus on the delivery of subject matter, but also in shaping character, instilling moral values, and fostering 21st century capabilities. Teachers are expected to be able to adapt to technological developments, be innovative in the learning process, and be a driver for the community in facing global disruption. This article comprehensively discusses the strategic role of teachers as agents of change in facing the challenges of educational globalization, obstacles faced in the field, and strategies that can be applied. This study was conducted through a literature review of various recent studies in Indonesia in the last five years. The results of the analysis show that teachers play a role as facilitators, innovators, motivators, and moral guides in building superior, adaptive, and characterful human resources in the midst of global trends.